Conveying different types of values via mathematical tasks - Cornelia Plunger; Anahit Yenokyan (Prometeica, 2023)
The purpose of this paper is to analyse possibilities of including and conveying a variety of values in teaching mathematics through tasks in terms of their openness. In the first part of the introduction we present the theoretical ideas about values in mathematics education by Bishop and Lim & Ernest. The second part of introduction sets out the reasons why an emphasis on values seems advisable. Mathematics is not commonly associated with a variety of values. However, for mathematical education an orientation towards societal demands appear relevant. Scholars like Skovsmose and Fischer alike demanded the development of a reflecting ability. Some national state curricula depict some of the societal demands by calling for an orientation towards general values for all school subjects, but in this we see discrepancies to practiced teaching. The section “Tasks and Values” relates to justifying why tasks appear to be a useful means of influencing mathematics education. Several scholars have already investigated the possibilities of different task-types for teaching values. Here we connect this purpose to tasks characterized by their varying openness. As teachers are essential to unfold the potential of tasks, the present analysis is intendent to give them concrete ideas for mediating values in mathematics classes. In the main part we analyse traditional tasks from ancient textbooks, with experiences in Armenian classes, as well as an open task with experiences of Austrian students in partner work. The discussed tasks provide opportunities for mathematical values like control, openness and for epistemological values as well as for more general values like self-confidence, mutual respect, justice and mathematics educational values like accuracy and consistency. In conclusion, the encouragement towards discussions among and with the students during the solving process of the task appears to be essential. Our experiences show that students mainly react positively towards such discussing activities. This could be a motivation for teachers to take up this issue besides of idealistic reasons.